Artificial Intelligence in Urban Planning: Smart Cities and Ethical Implications - Rao, . K. Koteswara; Deshpande, Renuka; K Shivakrishna, K Shivakrishna; Hegde N, Pratheeksha; G. Nagaraju, G. Nagaraju; T.V, Saroja (Journal of Neonatal Surgery, 2025)
With a rapid rate of growth, Artificial intelligence (AI) has changed urban planning into the creation of smart cities which have always sought to maximize infrastructure, service delivery and quality of life in cities. AI technologies support real-time analytics, predictive modeling, and autonomous decision making, empowering city planners to confront problems including congestion, energy efficiency, the environment and public safety. But such technological change has serious ethical stakes such as surveillance concerns and issues of inclusivity. This paper explores the intersection between AI and urban planning, discusses its role in smart city implementation; looks at existing work; gives an overview of methodologies; and discusses tangible and ethical issues. The study concludes with suggestions for ethical governance frameworks which can support an equitable and responsible integration of AI in urban planning.